Determination of loads in the evaluation of dynamic strength through elastic bands: Pilot Study (Revista horizonte, 2022)
The objective of the present investigation was to verify the application of the anthropometric body mass parameter in the evaluation of dynamic force using elastic bands. 36 healthy male and female volunteers participated, with different levels of physical conditioning, who underwent two strength tests, one with a bodybuilding machine and the other with elastic bands connected to a load cell, which enabled the determination of strength generated during the evaluation of the muscular condition of the pectoral, latissimus dorsi, quadriceps, hamstring groups; biceps and triceps. The results identified significant differences (p